TINGKAT KESUKAAN BAKSO IKAN DARI BERBAGAI BAHAN BAKU UTAMA DAGING IKAN PELAGIS BESAR - Junianto Junianto; Visivalery Nurerlindajava; Kemas Ahmad Akasyah Zaidan; Gibran Amalio Pranata (Universitas Muhammadiyah Gresik, 2024)
In the research conducted to assess the preference levels for fish meatballs made from various main ingredients, specifically pelagic fish such as tuna, mackerel, and skipjack, the study aimed to determine the preference for fish meatball products using large pelagic fish as the main ingredient, namely tuna, mackerel, and skipjack. Through a hedonic test, with results analyzed using the Friedman test, it was found that the panelists preferred fish meatballs made with mackerel as the main ingredient in terms of appearance, aroma, texture, and taste. The average scores for appearance were 5.93, for aroma 6.2, for texture 4.73, and for taste 5.4, which was the second highest after skipjack fish meatballs.